Evaluating the effectiveness of land and water integrative practices for achieving water sustainability within the Colorado River Basin: perceptions and indicators. Issue 2 (17th February 2022) - Quay, Ray; Sternlieb, Faith; Rauh, Eleanor; Andrade, Riley; Bartholomew, Anna; White, Dave; Holway, Jim; Sugg, Zachary; Rugland, Erin
ABSTRACT: Principle 12 of the OECD Principles on Water Governance calls for the evaluation of sustainable water policies, which to be effective must be salient, credible and legitimate. Using a 2021 survey of land and water managers within the Colorado River Basin, we examine the salience, credibility and legitimacy of two approaches to evaluate policies that integrate water and land management: using practitioners' perceptions of policies effectiveness to achieve water sustainability goals, and the importance of indicators to assess the water sustainability of a community. Results show perceptions of policy effectiveness and indicator importance vary with the context of organization and place.